Development of Social Capital Based on Health Promotion Model to Improve Behavior for Taking VIA Test - Tinuk Esti Handayani; Agung Suharto (Humanistic Network for Science and Technology (HNST), 2019)
VIA Test is an alternative screening examination of pap smears because it is usually inexpensive, practical, very easy to carry out and simple equipment and can be done by health professionals other than gynecology doctors. The purpose of this study was to prove the development of social capital-based health promotion to improve maternal behavior in following VIA Test to detect early cervical ces. This type of research was quasy experiment research with non equivalent pre test post test control group design, to analyze the influence of social capital-based health promotion to improve the behavior of mothers of fertile age couples in taking the VIA Test. The sampling technique was multistage random sampling with a sample size of 160. The independent variable of the research was a social capital-based health promotion module. The dependent variables were cognitive, perception, commitment and behavior for taking VIA Test. Data analysis were carried out by t-test and multiple linear regression test. Showed significant differences between pre test and post test on social capital, perception, commitment and behavior of mothers in taking the VIA test. There were a significant difference between intervention group 1 and control and intervention group 2 with control on cognitive, perception, commitment and behavior of mothers in taking VIA test. From the results of multiple linear regression analysis, it was found that the effect of social capital-based health promotion on maternal behavior in taking VIA Test was significant (p-value = 0.021). The influence of perception and commitment on maternal behavior in taking VIA Test was significant (p-value = 0.000). Keywords: social capital; perception; commitment; behavior